Can TIE-2 expressing monocytes represent a novel marker for hepatocellular carcinoma? - Dapas, Barbara; Grassi, Mario; Grassi, Gabriele (HepatoBiliary Surgery and Nutrition, 2014)
Hepatocellular carcinoma (HCC), the predominant form of primary liver cancer, is a global health problem representing the sixth most common cancer and the third cause of cancer related death worldwide. The number of deaths per year in HCC is comparable to the incidence number, underlying the aggressive behavior of HCC and the modest efficacy of available curative treatments. Effective HCC treatment is problematic also due to the lack of early and specific diagnostic markers. In this regard, particular interest has been put on the tyrosine kinase with Ig and endothelial growth factor (EGF) homology domains 2 (TIE2), a receptor of angiopoietins, predominantly present on endothelial cells but also observed on monocytes [TIE-2-expressing monocytes (TEMs)]. Recently, a work by Matsubara et al. showed that the amount of circulating TEMs is higher in hepatitis virus C (HCV)/HCC patients compared to HCV patients or healthy subjects. Additionally the authors showed that TEMs have a diagnostic potential for HCC. Whereas the molecular mechanisms responsible for this observation remain elusive and further studies are necessary to confirm this finding, the work of Matsubara et al. may contribute to the identification of a novel HCC prognostic and diagnostic marker.